The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1152/japplphysiol.00928.2018
|View full text |Cite
|
Sign up to set email alerts
|

Modifiability of the history dependence of force through chronic eccentric and concentric biased resistance training

Abstract: The increase and decrease in steady-state isometric force following active muscle lengthening and shortening are referred to as residual force enhancement (RFE) and force depression (FD), respectively. The RFE and FD states are associated with decreased (activation reduction; AR) and increased (activation increase; AI) neuromuscular activity, respectively. Although the mechanisms have been discussed over the last 60 years, no studies have systematically investigated the modifiability of RFE and FD with trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 82 publications
4
26
1
Order By: Relevance
“…In accordance with previous studies (Burnley, Vanhatalo, & Jones, 2012;Pethick, Winter, & Burnley, 2018;Theurel & Lepers, 2008), we considered that doublet torque is an index of peripheral fatigue and VA is an index of central fatigue in the current study. For the dorsiflexors, complete VA is often observed during MVC (Baudry et al, 2007;Chen & Power, 2019;Cheng & Rice, 2009), and this study also found "near maximal activation" throughout ( Figure 1c) as expected. Thus, it is suggested that voluntary drive was maintained and did not explain task failure in the current study.…”
Section: R5 R10supporting
confidence: 85%
See 2 more Smart Citations
“…In accordance with previous studies (Burnley, Vanhatalo, & Jones, 2012;Pethick, Winter, & Burnley, 2018;Theurel & Lepers, 2008), we considered that doublet torque is an index of peripheral fatigue and VA is an index of central fatigue in the current study. For the dorsiflexors, complete VA is often observed during MVC (Baudry et al, 2007;Chen & Power, 2019;Cheng & Rice, 2009), and this study also found "near maximal activation" throughout ( Figure 1c) as expected. Thus, it is suggested that voluntary drive was maintained and did not explain task failure in the current study.…”
Section: R5 R10supporting
confidence: 85%
“…Two supramaximal doublet stimulations at 100 Hz were interpolated approximately 2 s after the beginning and end of contraction, respectively, for VA assessment using the following formula: VA (%) = [1 − (interpolated twitch torque/control twitch torque)] × 100. Activation value of 95% VA or higher was deemed “near maximal” (for details please see Chen & Power, ), and all participants met this condition before the fatiguing task. The reliability and validity of the ITT were ensured elsewhere (Behm, St‐Pierre, & Perez, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study by Siebert et al 16 observed no significant modifiability of rFE with resistance training compared to recreationally active controls. 16 A later study by Chen and Power 17 observed an increase in residual torque enhancement following 4 weeks of concentric dorsiflexion training and a decrease following eccentric training, but no changes in residual torque depression ("torque" is used here because ankle joint torque data were collected using a multi-joint dynamometer, like in the present study; for simplicity's sake, rFD and rFE are used throughout this article to refer to torque data as well). Chen and Power's approach was rooted in the idea of modifying muscle fascicle length, which is believed to at least somewhat reflect serial sarcomere number.…”
Section: Introductionmentioning
confidence: 85%
“…Pennation angle and fascicle length were determined in accordance with previous studies. 17,32,34 The angle between the fascicle and central aponeurosis was defined as pennation angle, and fascicle length was calculated in each image as the inter-aponeurosis distance divided by the sine component of pennation angle in each image ( Figure 1D). Here, the averaged inter-aponeurosis distance from the proximal, center, and distal ends of the image was used in calculations.…”
Section: Ultrasoundmentioning
confidence: 99%